A non-absorbing organic redox couple for sensitization-based solar cells with metal-free polymer counter electrode. (1st October 2018) - Rahman, Md. Mahbubur; Wang, Jia; Nath, Narayan Chandra Deb; Lee, Jae-Joon
Abstract: An organo-sulfur compound, 5-methylthio-1, 3, 4-thiadiazole-2-thiol and its oxidized dimer 5-methylthio-1, 3, 4-thiadiazolium disulfide dication are used as a novel and universal redox couple in both dye-sensitized and quantum-dot sensitized solar cells, in conjunction with a conducting poly(3, 4-ethylenedioxythiophene) counter electrode. The 5-methylthio-1, 3, 4-thiadiazole-2-thiol/5-methylthio-1, 3, 4-thiadiazolium disulfide dication redox couple is low-cost and easily processable, and exhibits non-absorption of visible light, showing improved redox behavior at an electrochemically deposited poly(3, 4-ethylenedioxythiophene) counter electrode. Its redox potential is ca. 60 mV negatively and ca. 170 mV ( vs. normal hydrogen electrode) positively positioned than those of iodide/tri-iodide and polysulfide electrolytes, respectively. The maximum power conversion efficiency of (3.55 and 1.20) % is obtained in dye and quantum-dot sensitized solar cells, respectively, sensitized by 5-[[4-[4-(2, 2-Diphenylethenyl) phenyl]-1, 2, 3, 3a, 4, 8b hexahydrocyclopent [b] indol-7-yl] methylene]-2-(3-octyl-4-oxo-2-thioxo-5-thiazolid dye and CdS-quantum dot, respectively, together with the optimized poly(3, 4-ethylenedioxythiophene) counter electrode. These results clearly outperform the performance of identical dye and quantum-dot sensitized solar cells with Pt and Cu2 S-counter electrodes. Thus, this new redox couple and poly(3, 4-ethylenedioxythiophene) counter electrode pair is expected to offer a promising and universal alternative to the conventional iodide/tri-iodide and polysulfide electrolytes for sensitization-based solar cells. Graphical abstract: Image 1 Highlights: A novel non-absorbing organosulfur redox couple MTDT/MTDD 2+ was developed for DSSCs and QDSSCs. The MTDT/MTDD 2+ and PEDOT-CE conjugate outperformed the performance of identical DSSCs and QDSSCs with Pt and Cu2 S-CEs. PEDOT was deposited on FTO by electrochemical method. Improved PCEs of (3.55 and 1.20) % were attained in DSSCs and QDSSCs, respectively.